Doing contextual theology - Pears, Angela (Routledge, 2010)
The contextual nature of theology -- Starting from base : the roots of contemporary liberation theology in Latin America -- Gender matters : feminist informed theologies -- Further contexts of liberation the multiplicity of liberation theologies -- Postcolonial theologies -- Contextuality in critical perspective